2003
DOI: 10.1111/j.1744-7410.2003.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of intracerebral ocelli in two species of North American crayfish: Orconectes limosus (Cambaridae) and Pacifastacus leniusculus (Astacidae)

Abstract: Among rnalacostracan crustaceans, intracerebral ocelli were first discovered in Isopoda, but they have been more recently reported from a crayfish (Cherax destructor) and a sandhopper (Talitrus saltator). This electron microscopic study increases the number of crayfish t a m in which intracerebral ocelli are now known to occur by two: Astacidae and Cambaridae. These photoreceptors are always integrated into the anteromedio-dorsal part of the brain and are not visible externally. Each ocellus is made up of 4-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…We refer to these regions as the brain photoreceptor neuropils (BPNs) in this paper. Electron microscope studies have also shown the presence of rhabdomeric structures in Cluster 6 cells in the brains of the astacid (northern hemisphere) crayfish Orconectes limosus and Pacifastacus leniusculus (Bobkova et al, 2003). These cells, however, do not contain the dark screening pigment granules found in C. destructor.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…We refer to these regions as the brain photoreceptor neuropils (BPNs) in this paper. Electron microscope studies have also shown the presence of rhabdomeric structures in Cluster 6 cells in the brains of the astacid (northern hemisphere) crayfish Orconectes limosus and Pacifastacus leniusculus (Bobkova et al, 2003). These cells, however, do not contain the dark screening pigment granules found in C. destructor.…”
Section: Introductionmentioning
confidence: 88%
“…These cells, however, do not contain the dark screening pigment granules found in C. destructor. While the structure of these cells is entirely consistent with that of the brain photoreceptors of C. destructor (Bobkova et al, 2003), physiological recordings have not yet been made of their responses to light.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The pigment granules within the BPR-cell clusters in other crayfish species such as O. limosus, P. leniusculus, and P. clarkii are, unfortunately, not as easily visible but recognised only by electron microscopy (302). It is not known whether the pigment granules within BPRs migrate in a similar way, as do those of the PP in the retinular cells (185,17,302). BPRs are histamine-ir and express cryptochrome (CRY, see also 4.3.4.…”
Section: Extraretinal Brain Photoreceptorsmentioning
confidence: 99%
“…Freshwater crayfish featured early in studies of crustacean compound eyes (parker 1891) and the visual centres in the brain have also been the subjects of numerous structural and optical studies (e.g., by Krebs 1972;Vogt 1975;Land 1978;Bryceson 1986;Frixione & perez-olvera 1991;Sandeman et al 1991;hafner & Tokarski 1998;Bobkova et al 2003). Biochemical and physiological experiments were carried out by arechiga et al (1973), walcott (1974), cummins & Goldsmith (1981), cronin & Goldsmith (1982, Eccles et al (1983), and Kashiwagi et al (2000) and results from behavioural observations have recently been summarised by delgado- Morales et al (2004).…”
Section: Discussionmentioning
confidence: 99%